Intravitreal bevacizumab injection in advanced retinopathy of prematurity. - Choovuthayakorn J. (2014)
To report the efficacy of intravitreal bevacizumab injection for advanced retinopathy of prematurity (ROP) patients. A retrospective chart review was performed for 19 advanced ROP patients (34 eyes), who had intravitreal bevacizumab injection between January 1, 2007 and July 31, 2009 at Chiang Mai University Hospital. The baseline characteristics including gestational age, postmenstrual age of first injection, anterior and posterior segment changes, and complications between treatments to 1-year followed-up were analyzed. The patients were divided into 2 groups according to the indications for treatment. Group 1, two patients (4 eyes), received initial intravitreal bevacizumab injection followed by laser photocoagulation due to aggressive posterior disease. Group 2, seventeen patients (30 eyes), received intravitreal bevacizumab injection due to persistence of the vascular activity after laser treatment. There were statistical significant difference between the two groups in terms of a mean gestation age, a mean birth weight, and a mean time for first intravitreal injection (p = 0.002, 0.008, and 0.007 respectively). However, there was no statistical significant difference between the two groups in terms of timing for resolution of vascular activity and retinal vasculogenesis across the laser scar (p = 0.172). One patients with aggressive posterior disease progressed to stage 4A ROP with successful anatomical attachment by pars plana vitrectomy. At 1-year follow-up, no other ocular or systemic side effects were observed. There was no statistical significant difference of a mean spherical equivalent between the two groups (p = 0.280). Intravitreal bevacizumab injection is an effective procedure either as an adjuvant or initial treatment in advanced ROP cases.